Design, implementation and application of the Marchenko plane-wave algorithm - Thorbecke, Jan; Almobarak, Mohammed; IJsseldijk, Johno van; Brackenhoff, Joeri; Meles, Giovanni; Wapenaar, Kees (Computers & geosciences, 2024)
The Marchenko algorithm can suppress the disturbing effects of internal multiples that are present in seismic reflection data. To achieve this, a set of coupled equations with four unknowns is solved. These coupled equations are separated into a set of two equations with two unknowns using a time window. The two unknown focusing functions can be resolved by an iterative or direct method. These focusing functions, when applied to reflection data, create virtual point-sources inside the medium. Combining individual virtual point-sources into a plane-wave leads to an efficient computation of images without internal multiples. In this study the internal multiples are eliminated in a redatuming step which is part of the imaging algorithm. To use the Marchenko algorithm with plane-wave focusing functions, the time window that separates the unknowns must be adapted. The design of the plane-wave Marchenko algorithm is explained and illustrated with numerically modeled and measured reflection data. •Internal multiple removal based on Marchenko algorithm.•Efficient data processing by constructing plane-waves.•Explanation of counter intuitive time-windows.•Results are reproducible with provided source-code.